2002
DOI: 10.1161/01.atv.0000017703.87741.12
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Ischemic Events in the Brain and Heart Adapt the Hearts of Severely Atherosclerotic Mice to Ischemia

Abstract: Abstract-To investigate if spontaneous ischemic events in mice with severe multi-organ atherosclerosis could adapt to ischemia, apolipoprotein E/LDL receptor knockout mice were fed an atherogenic diet for 7 to 9 months. Signs of spontaneous ischemia occurred. One to two days later, hearts were excised, Langendorff-perfused with induced global ischemia, and compared with mice without signs of disease. In vivo heart or brain infarctions were verified by heart histology and/or increased serum levels of cardiac tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 28 publications
3
34
0
2
Order By: Relevance
“…The concept of RPC extends memory from a temporal storage of information to a spatial storage of information because the recognition of ischemia and reperfusion in one tissue is transferred to a virginal tissue not subjected to such preceding episodes (17). Although circulating humoral factors and neuronal mechanisms are involved in the initiation and transfer of such information (3,6), our study shows that the information is memorized within the explanted heart independently of ongoing humoral and neuronal stimulation.…”
Section: Discussionmentioning
confidence: 70%
“…The concept of RPC extends memory from a temporal storage of information to a spatial storage of information because the recognition of ischemia and reperfusion in one tissue is transferred to a virginal tissue not subjected to such preceding episodes (17). Although circulating humoral factors and neuronal mechanisms are involved in the initiation and transfer of such information (3,6), our study shows that the information is memorized within the explanted heart independently of ongoing humoral and neuronal stimulation.…”
Section: Discussionmentioning
confidence: 70%
“…Only healthy mice without skin injuries and no neurological deficit were accepted for the study (Tokuno et al, 2002). WT and KO mice were heparinised and anesthetised with a mixture of fluanisonum, fentaylum and midazolam (2.5, 0.08 and 1.25 mg kg À1 , respectively, i.m.).…”
Section: Animal Preparationmentioning
confidence: 99%
“…These data agree with those previously observed in the explanted rat heart and suggest that opening mK ATP channels produces an energy-sparing effect during sustained ischemia in heart and skeletal muscle. These data also suggest that mK ATP channels are both a trigger and mediator of acute remote IPC in hindlimb skeletal muscle of rats and pigs.Despite a number of papers suggesting that remote IPC performed in different organs results in acute protection of distant organs against infarction, only two previous papers (19,20) suggested that remote IPC can result in delayed protection 24 -72 h later, similar to that of delayed IPC because of a local IPC stimulus. Wang et al (20) showed that intestinal preconditioning by ischemia resulted in a protective effect against myocardial infarction 24 h later and that this effect was…”
mentioning
confidence: 98%
“…Despite a number of papers suggesting that remote IPC performed in different organs results in acute protection of distant organs against infarction, only two previous papers (19,20) suggested that remote IPC can result in delayed protection 24 -72 h later, similar to that of delayed IPC because of a local IPC stimulus. Wang et al (20) showed that intestinal preconditioning by ischemia resulted in a protective effect against myocardial infarction 24 h later and that this effect was mediated by inducible NO synthase (iNOS) based upon its blockade by two relatively selective iNOS inhibitors, aminoguanidine and S-methylthiourea.…”
mentioning
confidence: 98%
See 1 more Smart Citation